Beyond the Icon Asian American Graphic Narratives - Ty, Eleanor (The Ohio State University Press, 2022)
Demonstrates how contemporary Asian American creators employ graphic narrative to counter harmful misrepresentations and show Asian Americans as complex, nuanced individuals.